The effect of awareness program on fatigue among shift workers in electronics manufacturing industry - Mohd Shahril, Abu Hanifah; Norazura, Ismail (Institution of Engineering and Technology, 2022)
Shift workers in the electronics manufacturing industry are exposed to fatigue that can lead to accidents at work if not handled properly. This study aims to evaluate the effectiveness of a fatigue awareness program on shift workers in an electronics manufacturing factory. This quasi-experimental study involved 77 shift workers. A group of shift workers were assigned into case and control groups where the program was implemented in the case group only. The Multidimensional Fatigue Inventory was used to assess fatigue among the respondents. The result showed that there was a decrease in the prevalence and mean scores of all fatigue dimensions before and after the implementation of the program in the case group. There was a statistically significant difference between mean scores of general fatigues before and after the program (p = 0.023) in the case group. It was found that fatigue intervention has a small effect (Cohen’s d = 0.389) on general fatigue score. This study proves that an awareness program can reduce the incidence of fatigue among shift workers. However, more prevention approaches should also be implemented to greatly reduce the incidence of fatigue among shift workers in the electronics manufacturing industry.